Identification of Campylobacter jejuni isolates from cloacal and carcass swabs of chickens in Thailand by a 5′ nuclease fluorogenic polymerase chain reaction assay - Padungtod P. (2014)
A rapid 5′ nuclease fluorogenic polymerase chain reaction (PCR) assay for identifying Campylobacter jejuni was applied to Campylobacter isolates from chicken cloacal and carcass swabs collected from three chicken farms and a slaughterhouse in Thailand. The primers and the probe were based on the sequence of the gyrA gene in C. jejuni. C. jejuni isolates were identified by fluorogenic PCR assay of bacterial cells directly from Campylobacter-selective agar medium. This assay allowed the identification of C. jejuni within 1 day after colonies appeared on selective media. The fluorogenic PCR assay yielded results comparable to those of the conventional test kit (kappa = 0.76) but required less time. When the two methods disagreed with regard to species identification, results were confirmed by PCR restriction fragment length polymorphism of 23S rRNA genes. In these instances, the fluorogenic PCR assay correctly identified more isolates of C. jejuni than did the conventional test kit (six of seven isolates were unidentifiable by the conventional test kit). The fluorogenic PCR assay is a rapid and specific method that outperforms the conventional test kit in the identification of C. jejuni from environmental samples.